Membatik Jumputan Dalam Meningkatkan Kreativitas Anak (BIDAYAH: STUDI ILMU-ILMU KEISLAMAN, 2017)
This study aims to determine the proces of improving children aged 5-6 years-old’s creativity through batik jumputan in AL-HUSNA Playgroup, Sobang Cikuning Kampung Lebak District of Sobang Propensi Banten. The study was conducted from August to October 2015. The model used in this research is classroom action researh. Research phase includes planning, implementation, observation, and reflection. The participants of the study were children aged 5-6 years-old in AL-HUSNA Playgroup, Sobang that were lacked in creativity. Results on prasiklus acquisition of 38,4% and then increased in the first cycle by 15% with the average value reached 63,1% grade. And the second cycle percentage class average value to 89,8% which means an increase in comparison to the stage if persiklus.